Time reversibility concepts, the second law and irreversible thermodynamics - Jesudason, C.G. (2011)
Time reversibility concepts and transformations are first reviewed and difficulties with the standard formulations indicated. The kinetic equations which were constructed to exhibit reciprocity relations in their transition probabilities based on time reversal ideas are examined next and a first principle analysis shows that the standard forms are not in accord with the first principles. A thermodynamical theory based on the Kelvin-Clausius-Planck definition of entropy and a modified form of the Benofy and Quay postulate concerning conductive heat is developed and reciprocity and other relations are derived as an example of one possible alternative to the standard treatments with their indicated inconsistencies.